RESCUER: Development of a Modular Chemical, Biological, Radiological, and Nuclear Robot for Intervention, Sampling, and Situation Awareness*. Issue 7 (2nd June 2015) - Guzman, Roberto; Navarro, Roman; Ferre, Juan; Moreno, Miguel
Abstract : This paper describes the development of a robot prototype for intervention, sampling, and situation awareness in CBRN (chemical, biological, radiological, and nuclear) missions. It outlines the mission requirements, design specifications, the solutions that were developed and integrated, and the final tests done. The solution addresses one of the most important mission requirements in CBRN scenarios: the capability to decontaminate the robot once it has been used in real missions. As microdoses of CBRN contaminants are sufficient to cause significant damage to human beings, prevention of robot contamination is always of top priority. If there is a potential danger of real contamination, it can only be removed by effective decontamination. The way to deal with this problem imposes significant design conditions; the proposed design allows an easy and fast decontamination of the robot. The work presents a new way to approach this kind of robot, based on modular component architecture over a robot operating system that permits the attachment and detachment of robot components via unique electromechanical interfaces. The resulting modular robot introduces an innovative kinematic solution that can be dynamically configured for the different mission requirements.